The relationship between nurse–nurse collaboration and work readiness among new graduate nurses - Tarhan, Merve; Doğan, Pınar; Kürklü, Ahu (John Wiley and Sons Inc, 2022)
Background: Communication and collaboration with colleagues are crucial for new graduate nurses (NGNs) because of the adaptation to both the healthcare system and professional role. Therefore, working units with effective collaboration among nurses may increase new graduates' work readiness. Aim: This study aimed to determine the relationship between the perceptions of nurse–nurse collaboration and the work readiness level among NGNs. Methodology: This descriptive, cross-sectional study was carried out with 198 NGNs in four private hospitals affiliated with a university. A self-administered questionnaire, including a personal information form, the Nurse–Nurse Collaboration Scale, and Work Readiness Scale, was used to collect data. Data analysis was performed using descriptive tests, and Spearman's rank correlation coefficients. Results: NGNs had moderate perceptions of nurse–nurse collaboration, with a median score of 2.46 (2.23–2.88) out of 4. Work readiness among NGNs was moderate, with a median score of 304 (270–332) out of 460. There was a statistically significant correlation between nurse–nurse collaboration and work readiness (rs = 0.26; p <.001). Conclusion: The results of this study demonstrated that improving nurse–nurse collaboration is an effective way to increase work readiness among NGNs.
Keywords: Interdisciplinary Communication; Interpersonal Relations; Nurses; Work Readiness